2004
DOI: 10.1007/bf03181535
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of three-dimensional flow structures in the wake of an inclined circular cylinder

Abstract: In the previous measurements of the aerodynamic sound generated from an inclined circular cylinder, it is reported that the sound pressure level (SPL) changes with the aspect ratio and the inclined angle. Therefore, we have investigated the changes in the vortex structure of the wake considered as one of the causes of the SPL variation. Using the low-noise wind tunnel, the velocity fluctuation in the wake is measured to obtain the correlation length. Moreover, the flow visualization is performed with a hydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 10 publications
1
2
0
2
Order By: Relevance
“…At a large yaw angle, such as 45 • , it even becomes a wedge shape lying on the tip end. Compared with the experiments [25], the numerical simulation is consistent with the experimental flow visualization.…”
Section: Wake Vortex Structuresupporting
confidence: 71%
“…At a large yaw angle, such as 45 • , it even becomes a wedge shape lying on the tip end. Compared with the experiments [25], the numerical simulation is consistent with the experimental flow visualization.…”
Section: Wake Vortex Structuresupporting
confidence: 71%
“…Ramberg (1983) described the impacts of the inclination angle on a cylinder using the independence principle (IP) or Cosine Law, which stated that the flow with free-stream velocity U past a cylinder with an inclination angle  could be regarded as a normal-incidence case with a flow velocity of cos n UU  = while the contribution from its axial component could be ignored. Matsuzaki et al (2004) experimentally studied the flow past an inclined cylinder in a low-noise wind tunnel with a hydrogen bubble method and pointed out that the Strouhal number deviated from the IP at 15   . Thakur et al (2004) found in their experiment that the wake vortices of a stationary cylinder showed a similar quasi-two-dimensional state for 0 60     .…”
Section: Introductionmentioning
confidence: 99%
“…Matsuzaki et al (2004) employed hydrogen bubble method for visualization of flow structures in the wake of an inclined circular cylinder. Jang et al (2007) investigated turbulent structure in the wake of a sphere using smoke-wire method.…”
Section: Introductionmentioning
confidence: 99%